Les fables Canadiennes de Jules Verne : discorde et concorde dans une autre amérique - Fabre, Gérard (Collection Amérique française., 2018)
Gérard Fabre offers a socio-literary analysis of three Canadian novels by Jules Verne and invites us to discover the place that Canada and Quebec occupied in French imagination at the time.